Limit Equilibrium And Finite Element – Shear Strength Reduction Stability Analysis, Kota Bunyih Yailings Dam, Pengkalan Hulu, Perak, Malaysia¬¬ - Agam, Maclive Wilkinson (2018)
A slope stability study of Kota Bunyih (KB) tailings dam, Pengkalan Hulu was conducted to qualitatively analyse the reliability and stability of the KB tailings dam and to determine the factors of safety (FOS) under the loadings of steady-state seepage and seismic conditions by using Limit Equilibrium Methods (LEM) and Finite Element Method-Shear Strength Reduction (FEM SSR). In addition, the determination of the probability of failure (PF) of KB tailings dam is also carried out using probability analysis under LEM and FEM SSR. The qualitative analysis of the existing design of KB tailings dams was conducted based on the desk study, site investigation and geotechnical laboratory tests. Slide 7.0 and RS2 9.0 programs were used to conduct the deterministic and probabilistic analyses of KB tailings dam under various loadings based on the geotechnical data obtained. Based on the qualitative analysis, it was found that the design of KB tailings dams was slightly deviated from the standard design and caused ponded water in certain locations that may increase the risk of piping phenomenon. Furthermore, based on the analysed particle size distribution (PSD) of soil samples of KB tailings dam, it was found that the aggregate of New Earth Blanket and New Dam structures did not meet the third criterion of filter design because the PSD of the materials are not smoothly graded. However, all of the FOS obtained from the analysis of the steady-state seepage condition under the LEM and FEM provide the FOS>1.5, and are considered as safe. However, the obtained FOS of pseudo-static seismic analysis for the downstream slope (FOS=1.22) was slightly less than the recommended minimum value of 1.25. The probability analysis by using Spencer method, Sarma method and FEM SSR have provided non-zero values of PF. However, the values of PF are very small (<1%) which indicate that only a few of critical slip surfaces have the FOS<1.5 thus directly not affecting the stability of the dam. Overall, although the slope stability of the KB tailings dam is considered safe based on the steady-state seepage and probabilistic analyses, the slope stability of KB tailings dam is found unsatisfactory based on qualitative and pseudo-static seismic analyses, and should be given more attention in the future.